1996
DOI: 10.1210/endo.137.11.8895383
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor production by Leydig cells: evidence for a role in the regulation of testicular function.

Abstract: Macrophage migration inhibitory factor (MIF), described originally as a product of activated T lymphocytes, recently has been found to be released by monocytes/macrophages and the anterior pituitary gland. Immunohistochemical studies of the adult rat testis using an affinity-purified polyclonal antimurine MIF antibody demonstrated strong staining for MIF in Leydig cells and their putative precursors. Peritubular myoid cells and the seminiferous epithelium were negative for MIF staining; however, a weak reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 20 publications
3
52
2
1
Order By: Relevance
“…It is constitutively expressed by a variety of cell types and in many tissues [21][22][23][24][25][26][27][28]. Renal MIF mRNA and protein expression is upregulated in different types of experimental kidney disease [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…It is constitutively expressed by a variety of cell types and in many tissues [21][22][23][24][25][26][27][28]. Renal MIF mRNA and protein expression is upregulated in different types of experimental kidney disease [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Bernhagen and his coworkers recently reported that MIF catalyzes the reduction of disulfides in insulin and small molecular weight substrates via transhydrogenase reactions (Kleeman et al 1998a). The three-dimensional structure of MIF is unlike any other cytokine (Sun et al 1996;Suzuki et al 1996b;Kato et al 1996), Weiser et al 1989Onodera et al 1997Juttner et al 1998Swope et al 1998Bacher et al 1996Apte et al 1998Mikayama et al 1993Calandra et al 1995Waeber et al 1997Meinhardt et al 1996Rosengren et al 1996Rosengren et al 1997Kleeman et al 1998 but bears striking similarity to the global architecture and local active site of two microbial enzymes (Subramanya et al 1996). These biological and structural observations have raised the intriguing possibility that MIF may have a dual role as a cytokine/hormone and enzyme.…”
Section: D Swope and E Lolismentioning
confidence: 99%
“…Recently, many reports have also suggested that MIF is considered to be an endocrine factor. 28,29 Interestingly, MIF has been demonstrated to have various kinds of catalytic activities; for example, tautomerase and oxidoreductase activity. 27,30,31 MIF is ubiquitously expressed in both immune and other cells, including various kinds of local tissues.…”
Section: Molecular Characteristics and Bioactivity Of Mifmentioning
confidence: 99%